Research on AR System of Preschool Science Activities from the Perspective of Artificial Intelligence - Zhufeng Ye; Jirarat Sitthiworachart (My University, 2022)
With the development of the economy and the improvement of living standards, artificial intelligence technology is gradually changing people's lives, and people's cognition of knowledge has undergone a new turn to a certain extent, which is undoubtedly a huge challenge to traditional education.Kindergarten education activities are compatible with the cultivation of young children by artificial intelligence, which promotes a new turn of cultivation goals and new changes in methods.Kindergarten education activities supported by artificial intelligence should be based on the development of young children, based on the needs of young children, and based on the experience of young children, and can use AR technology to realize kindergarten scientific activities.
Keywords: Medical Research and Treatments